The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
AIAA Guidance, Navigation, and Control Conference 2009
DOI: 10.2514/6.2009-6008
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Traffic Flow Management Decision Making

Abstract: A generalized approach is proposed to support integrated traffic flow management decision making studies at both the U.S. national and regional levels. It can consider tradeoffs between alternative optimization and heuristic based models, strategic versus tactical flight controls, and system versus fleet preferences. Preliminary testing was accomplished by implementing thirteen unique traffic flow management models, which included all of the key components of the system and conducting 85, six-hour fast-time si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Airspace capacity in the absence of weather is limited mostly by air traffic controller workload considerations. When traffic demand is expected to exceed capacity, traffic flow management techniques, [1][2][3][4][5][6][7] such as delaying fights on the ground, spacing them in the air and changing their routes of flight, are used to curtail demand. The delays cost the airlines and the flying public.…”
Section: Introductionmentioning
confidence: 99%
“…Airspace capacity in the absence of weather is limited mostly by air traffic controller workload considerations. When traffic demand is expected to exceed capacity, traffic flow management techniques, [1][2][3][4][5][6][7] such as delaying fights on the ground, spacing them in the air and changing their routes of flight, are used to curtail demand. The delays cost the airlines and the flying public.…”
Section: Introductionmentioning
confidence: 99%
“…Consider the discrete time dynamic system x k1 fx k ; v k y k gx k ; w k (1) where x k is the state of the model at the kth instant, y k is the measurement, f denotes the time-propagation function, v k is the process noise, and w k is the measurement uncertainty in the measurement model function g. It is assumed that their probability distributions are known. Let the accumulation of measurements up to the current time step k be denoted by Y k , i.e., Y k ≔ fy i ji 1; 2; : : : ; kg.…”
Section: A Bayes Filtermentioning
confidence: 99%
“…Several NASA efforts have investigated TFM using advanced iterative algorithms not only for strategic TFM in the National Airspace System (NAS) but also for managing surface traffic flows [1][2][3][4][5][6][7][8]. While these algorithms can provide precise solutions to the traffic management problem, they are more suitable for predictive control based on deterministic data.…”
Section: Introductionmentioning
confidence: 99%
“…These probabilities were shown in a previous study to be a reasonable surrogate for determining areas pilots would avoid flying through. 8 Clearly, other deviation probabilities can be used as Grabbe, et al, 10 found good results for their study of weather avoidance without considering aircraft conflicts using 60 percent CWAM deviation probabilities.…”
Section: B the Convective Weather Avoidance Modelmentioning
confidence: 99%